Anxiety, depression, and insomnia among medical and non-medical students in Jordan: a cross-sectional study - Jehad Feras AlSamhori; Diala Ra’Ed Kamal Kakish; Abdel Rahman Feras AlSamhori; Ahmad Feras AlSamhori; Noor Rajeh Abu Hantash; Afnan Firas Abu Swelem; Mamoun Hamed Ali Abu-Suaileek; Hazar Mohammed Arabiat; Mohammad Anwer Altwaiqat; Radwan Banimustafa; Abdallah Barjas Qaswal; Abdulqadir J. Nashwan (Middle East Current Psychiatry)
Abstract Background Depression, the leading cause of disability worldwide, has worsened due to the COVID-19 pandemic, with key risk factors including age, gender, and socioeconomic status. Jordan is experiencing an increase in mental health issues, particularly among children, adolescents, and university students, yet negative attitudes and structural barriers limit access to mental healthcare This study provides a comprehensive analysis of depression, anxiety, and sleep quality among Jordanian undergraduate students. Methods This cross-sectional study was conducted between December 2023 and March 2024. The study used the Generalized Anxiety Disorder scale (GAD-7), the Patient Health Questionnaire (PHQ-9), and the Insomnia Severity Index (ISI) to evaluate these mental health factors. Data collection involved a self-administered survey, distributed online and in paper format. Multiple linear regression was utilized to pinpoint significant predictors. Results A total of 1181 participants completed the survey, with an average age of 20.43 years. Among the respondents, 74.2% were female, and 35.1% were medical students. Predictors of GAD-7 scores included year of study for medical students, with PHQ-9 scores and male gender serving as negative predictors. For non-medical students, both PHQ-9 and ISI scores positively predicted higher GAD-7 scores. ISI scores were positively influenced by age and PHQ-9 scores for medical students, whereas for non-medical students, age, PHQ-9, and GAD-7 scores were positive predictors. Conclusion The study demonstrates that non-medical students experience higher levels of depression, insomnia, and anxiety than their medical counterparts. These findings highlight the necessity for targeted mental health interventions and awareness programs for all undergraduate students.